2020
DOI: 10.3390/ijms21218374
|View full text |Cite
|
Sign up to set email alerts
|

CaHsfA1d Improves Plant Thermotolerance via Regulating the Expression of Stress- and Antioxidant-Related Genes

Abstract: Heat shock transcription factor (Hsf) plays an important role in regulating plant thermotolerance. The function and regulatory mechanism of CaHsfA1d in heat stress tolerance of pepper have not been reported yet. In this study, phylogenetic tree and sequence analyses confirmed that CaHsfA1d is a class A Hsf. CaHsfA1d harbored transcriptional function and predicted the aromatic, hydrophobic, and acidic (AHA) motif mediated function of CaHsfA1d as a transcription activator. Subcellular localization assay showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 76 publications
(80 reference statements)
2
8
0
Order By: Relevance
“…The total RNA was isolated with Trizol reagent (TIANGEN, China) ( Gai et al., 2020 ). The first strand of cDNA was synthesized from 2μg of total RNA using the FastKing RT Kit (TIANGEN, China).…”
Section: Methodsmentioning
confidence: 99%
“…The total RNA was isolated with Trizol reagent (TIANGEN, China) ( Gai et al., 2020 ). The first strand of cDNA was synthesized from 2μg of total RNA using the FastKing RT Kit (TIANGEN, China).…”
Section: Methodsmentioning
confidence: 99%
“…Among various SOD enzymes, Cu/Zn-SOD is identified as the central component in regulating total SOD activity in rice anthers [ 12 ]. Previous studies have demonstrated the links between antioxidant enzymes and Hsfs in redox regulation [ 13 , 14 ]. PuHSFA4a increased glutathione S-transferase (GST) activity by binding to the promoter of PuGSTU17 in Populus ussuriensis to reduce ROS acumination and promote excess Zn tolerance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…PuHSFA4a increased glutathione S-transferase (GST) activity by binding to the promoter of PuGSTU17 in Populus ussuriensis to reduce ROS acumination and promote excess Zn tolerance [ 13 ]. Heterologous expression of CaHsfA1d in Arabidopsis enhanced the expression of Hsfs and the antioxidant gene AtGSTU5 , thereby maintaining H 2 O 2 homeostasis and improving plant thermotolerance [ 14 ]. However, Hsf-mediated redox regulation in pollen under heat stress is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress upregulated most HSR genes at the transcriptional level, which usually had opposite expression patterns under standard growth conditions. The overexpression of many of these HSR genes, such as DDF1 [ 27 ], ATHSFA2 [ 28 ], AT-HSFB2A [ 29 ], BIP3 [ 30 ], MIPS2 [ 31 ], HSP17.6II [ 32 ], HSP17.6B-CI [ 33 ], Hsp70b [ 34 ], HSP70 [ 35 ], and CYP71B2 [ 36 ], would facilitate improved tolerance to heat stress. Thus, we conclude that the overexpression of HSR genes during heat stress may contribute to BrPP5.2-mediated heat stress tolerance.…”
Section: Discussionmentioning
confidence: 99%